Trypanosoma cruzi High Mobility Group B (TcHMGB) can act as an inflammatory mediator on mammalian cells - Cribb, Pamela (2017)
Background: High Mobility Group B (HMGB) proteins are nuclear architectural factors involved in chromatin remodeling and important nuclear events. HMGBs also play key roles outside the cell acting as alarmins or Damage-associated Molecular Patterns (DAMPs). In response to a danger signal these proteins act as immune mediators in the extracellular milieu. Moreover, these molecules play a central role in the pathogenesis of many autoimmune and both infectious and sterile inflammatory chronic diseases. Principal findings: We have previously identified a High mobility group B protein from Trypanosoma cruzi (TcHMGB) and showed that it has architectural properties interacting with DNA like HMGBs from other eukaryotes. Here we show that TcHMGB can be translocated to the cytoplasm and secreted out of the parasite, a process that seems to be stimulated by acetylation. We report that recombinant TcHMGB is able to induce an inflammatory response in vitro and in vivo, evidenced by the production of Nitric Oxide and induction of inflammatory cytokines like TNF-α, IL-1β and IFN-γ gene expression. Also, TGF-β and IL-10, which are not inflammatory cytokines but do play key roles in Chagas disease, were induced by rTcHMGB. Conclusions: These preliminary results suggest that TcHMGB can act as an exogenous immune mediator that may be important for both the control of parasite replication as the pathogenesis of Chagas disease and can be envisioned as a pathogen associated molecular pattern (PAMP) partially overlapping in function with the host DAMPs.